Platelet HMGB1 is required for efficient bacterial clearance in intra-abdominal bacterial sepsis in mice - Zhou, Hui (Blood Adv, 2018)
Thrombocytopenia impairs host defense and hemostasis in sepsis. However, the mechanisms of how platelets regulate host defense are not fully understood. High-mobility group box 1 (HMGB1), a danger-associated molecular pattern protein, is released during infection and contributes to the pathogenesis of sepsis. Platelets express HMGB1, which is released on activation and has been shown to play a critical role in thrombosis, monocyte recruitment, and neutrophil extracellular trap (NET) production. However, the contribution of platelet HMGB1 to host defense is unknown. To determine the role of platelet HMGB1 in polymicrobial sepsis, platelet-specific HMGB1 knockout (HMGB1 platelet factor 4 [PF4]) mice were generated and were subjected to cecal ligation and puncture (CLP), a clinically relevant intra-abdominal sepsis model. Compared with HMGB1 Flox mice and wild-type (WT) mice, HMGB1 PF4 mice showed significantly higher bacterial loads in the peritoneum and blood, an exaggerated systemic inflammation response, and significantly greater mortality after CLP. Deletion of HMGB1 in platelets was associated with lower platelet-derived chemokines (PF4 and RANTES) in the peritoneal cavity, and a decrease of platelet-neutrophil interaction in the lung after CLP. In vitro, neutrophils cocultured with activated HMGB1 knockout platelets showed fewer platelet-neutrophil aggregates, reduced reactive oxygen species (ROS) burst as compared with control. Taken together, these data reveal an unrecognized role of platelet HMGB1 in the regulation of neutrophil recruitment and activation via modulation of platelet activation during sepsis.